PENGARUH KEPEMIMPINAN, MOTIVASI DAN TIM KERJA TERHADAP KINERJA KARYAWAN DI NEO HOTEL MANGGA DUA SQUARE - Mochammad Rikki Dwi Firdana; Aris Budiono (LPPM Universitas Asa Indonesia, 2017)
Purpose- This study aims to determine the effect of leadership, motivation and work teams on employee performance at Neo Hotel Mangga Dua Square Design/methodology/approach- The type of data in this study is primary or data originating from respondents who contain respondents' opinions about the dimensions of leadership, motivation, work team and performance. Data collection can be through the questionnaire instrument. The population in this study were all Neo Hotel Mangga Dua Square employees with a sample of 100 respondents and using saturated samples. The method of analysis uses descriptive and quantitative methods. Finding- The results of research on partial variables, the value of t count is greater than t table, then Ha shows and states there is a positive and significant influence between leadership, motivation and team work to the performance. While the percentage of influence on the leadership, motivation and team work on employee performance at Neo Hotel Mangga Dua Square amounted to 26.21%, while the rest influenced by other variables such as planning factors, organizing factors and others.